Wind shear coefficients and energy yield for Dhahran, Saudi Arabia - Rehman, Shafiqur (2020)
Abstract This study presents calculated values of wind shear coefficients (WSE) using measured values of wind speed at 20, 30, and 40m above ground level (AGL), for Dhahran, Saudi Arabia. The study also includes the air density estimated using measured air temperature and surface pressure and effect of wind shear coefficient on energy yield from a wind farm of 60MW installed capacity developed using 40 wind turbines of 1500kW size. The data used in the determination of wind shear coefficient covered a period of almost 5 years between 4 October 1995 and 30 November 2000. The study suggests a value of 0.189 of wind shear coefficient for the calculation of wind speed at different heights if measured values are known at one height. No regular seasonal trend was observed in the values of wind shear coefficients. In case of diurnal variation, higher values were observed during nighttime and early hours of the day and comparatively smaller values during day light hours. The air density, calculated using measured temperature and pressure was found to be 1.18 kg/m3. The energy yield obtained using RetScreen software, showed that the actual wind shear coefficient presented in this paper produced around 11–12% more energy compared to that obtained using 1/7 power law. Accordingly, 2–3% higher plant capacity factors were achieved using actual sitedependent wind shear coefficient instead of 1/7th wind power law exponent for the calculation of wind speed at hub-height. r 2006 Elsevier Ltd. All rights reserved. Keywords: Wind shear coefficients; Air density; Wind power potential; Wind farm; Wind speed; Wind energy